Prevention and management of urologic injury during gynecologic laparoscopy. Issue 4 (August 2016) - Findley, Austin D.; Solnik, M. Jonathon
Abstract : Purpose of review: This article provides an update on the best practices for the prevention, recognition, and management of urinary tract injuries that may occur during gynecologic laparoscopic surgery. Recent findings: Higher surgical volume is directly associated with improved surgical outcomes, denoted by consistently lower rates of complications for commonplace procedures such as hysterectomy. As a result, expert opinion on prevention of iatrogenic urologic injury suggests a real need for improved education and training of gynecologic surgeons. Discontinued manufacturing of indigo carmine has led to the utilization of alternative methods to assess ureteral patency during cystoscopy, such as phenazopyridine or sodium fluorescein. Intraoperative cystoscopy has been shown to detect approximately 50% of urinary tract injuries during hysterectomy, but has limited accuracy and does not necessarily decrease delayed postoperative complications. When identified, most urologic injuries can be managed in a minimally invasive fashion. Summary: A thorough understanding of pelvic anatomy and early recognition of urinary tract injuries can significantly reduce surgical morbidity for women undergoing laparoscopic surgery. Abstract : Supplemental Digital Content is available in the text